Potrzeby kadrowe oświaty, nowe programy szkolne a kształcenie i doskonalenie nauczycieli języka polskiego (Ekspertyza) = The staff requirements of the educational system, new syllabus designs at school versus under- and postgraduate studies of the teachers of Polish - Frycie, Stanisław; Podgórski, Wojciech (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The analysis of the problem pointed out by the litle of the present paper has constituted the basis for forrnulating the following conclusions:
Keywords: język polski - nauczanie; nauczyciele; badania